Encouraging Student Sense of Belonging Through Instructor Face Support - Nicholas R. Burk; Amy Pearson (Central States Communication Association, 2022)
Research has established important links between student sense of belonging in the classroom and levels of academic engagement, motivation, and persistence (e.g., Jang et al., 2016; Reeve, 2012) yet more work is needed to identify specific teacher communication tactics and strategies that can foster sense of belonging and increased engagement. Using a conceptual framework centered on organizational identification, we surveyed 172 undergraduates and found that instructor interpersonal skills-specifically face support during student feedback-significantly correlated with increased class identification and sense of belonging. These results hold important implications for promoting student engagement, motivation, and persistence, particularly for underrepresented students.